Cardiovascular risk and clinical factors in athletes: 10 years of evaluation - de Matos, L. D. N. J.; de Almeida Ordacgi Caldeira, N.; de sa Perlingeiro, P.; dos Santos, I. L. G.; Negrao, C. E.; Azevedo, L. F. (Medicine & Science in Sports & Exercise, 2011)
PURPOSE: Preparticipation screening in athletes is a very current but controversial theme. Part of this controversy is due to the cost benefit, especially when the screening is merely used as a prevention of sudden cardiac death caused by rare and hereditary diseases. The purpose of this study was to describe the prevalence of preexisting diseases, cardiovascular risk factor for cardiovascular diseases development, and hematological profile in a population of amateur and professional athletes.